Design a Dual Polarizations MIMO Antenna Based on Decoupling Elements for 5G Smart-Phones - Haider Saad; Mahmood F. Mosleh; Raed Abd-Alhameed (Journal of Techniques)
This paper suggests a compact linear and circular polarization MIMO antenna for sub-6 GHz 5G smartphones. The proposed design can be divided into three parts: Firstly, a linear polarized dipole antenna is presented with dimensions of 1×33.7×32.5mm3 and exhibits an impedance bandwidth (IBW) of 3.24GHz ranging from 3.3GHz to 6.6GHz at S11˂-10dB. The second part includes a circular polarization CPW-Fed antenna with dimensions of 1×23.2×30mm3. The IBW of the CPW antenna is more than 4GHz, starting from 3.9GHz to more than 8GHz at an S11˂-10dB. The 3-dB axial ratio for the CP CPW antenna ranges from 4GHz to 7.38GHz. Finally, a combination of LP and CP antennas is presented to form a dual polarization MIMO system. A MIMO system consists of 5 elements; 4 elements are LP and 1 element is a CP antenna. The size of the MIMO system is 1×82.5×150mm3 printed on an FR-4 substrate. Two impedance bandwidths are found due to the use of two antenna types. The first one (S11, S22, S44, S55) equals 3.44GHz while the second (S33) equals 4.33GHz. HFSS is used for designing and simulating the proposed structures, while CST is used for verifying the results.